2012
DOI: 10.1007/s10578-012-0314-1
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Among Children and Adolescents in Iran: A Confirmatory Factor Analytic Study of the Centre for Epidemiological Studies Depression Scale for Children

Abstract: This study investigated the psychometric properties of the Iranian translation of the Centre for Epidemiological Studies Depression Scale for Children (CES-DC) in school children and adolescents in Iran. The CES-DC is a 20-item self-report scale designed to measure depressive symptoms in children and adolescents. A total of 1,984 children and adolescents, aged 12-17 years, participated in this research. In addition to the CES-DC, all participants completed the Spence Children's Anxiety Scale (SCAS) and the Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 33 publications
7
47
4
Order By: Relevance
“…Besides the factor structure, the results regarding the correlations of Bulgarian version of CES-DC and subscale scores with the SDQ, the SCAS provided some evidence for convergent validity. Consistent with the previous studies (e.g., Essau et al, 2012;Tsocheva et al, 2013), scores on the SDQ and SCAS scales were found significantly associated with CES-DC scores in the expected directions in this sample of Bulgarian adolescents. The results showed that a high level of depression in adolescents is associated with high levels of emotional and behavioral problems.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Besides the factor structure, the results regarding the correlations of Bulgarian version of CES-DC and subscale scores with the SDQ, the SCAS provided some evidence for convergent validity. Consistent with the previous studies (e.g., Essau et al, 2012;Tsocheva et al, 2013), scores on the SDQ and SCAS scales were found significantly associated with CES-DC scores in the expected directions in this sample of Bulgarian adolescents. The results showed that a high level of depression in adolescents is associated with high levels of emotional and behavioral problems.…”
Section: Discussionsupporting
confidence: 92%
“…The Cronbach Alpha of the CES-DC in the present study was found for age to be .89 for the total CES-DC score. Also, consistent with previous studies (e.g., Essau et al 2012), the CES-DC subscales with the lowest and highest Cronbach Alphas were those of "positive affect" and "depressed affect" subscales, respectively. Moreover, in line with the previous findings (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This limitation is partially mitigated by multiple informants reporting on youths' emotional symptoms at Time 1. Further, this subscale is reliably associated with validated measures of adolescent depression and predicts children and adolescents' depressive symptoms (Alpaslan et al 2016;Essau et al 2013;Goodman 2001;Goodman et al 2003;Muris et al 2003;Tsang et al 2012). YR-ES and PR-ES at Time 1 were also strongly related to YR-DS at Time 2.…”
Section: Limitationsmentioning
confidence: 90%
“…Externalizing problems such as conduct problems (Keenan & Shaw, ; Maughan, Rowe, Messer, Goodman, & Meltzer, ), oppositional defiant behavior (Boylan, Vaillancourt, Boyle, & Szatmari, ; Loeber, Burke, Lahey, Winters, & Zera, ; Munkvold, Lundervold, Lie, & Manger, ), attention deficit‐hyperactivity disorder (ADHD), and peer problems (Zahn‐Waxler, Shirtcliff, & Marceau, ) show a marked male preponderance. On the other hand, internalizing problems such as depressive/mood disorders, anxiety disorders, emotional problems, and PTSD show a marked female majority (Barkmann, Erhart, & Schulte‐Markwort, ; Bettge, Wille, Barkmann, Schulte‐Markwort, & Ravens‐Sieberer, ; Essau, Olaya, Pasha, Gilvarry, & Bray, ).…”
mentioning
confidence: 99%